A Rare Case of Bilateral Chronic Dacryocystitis: Secondary to Punctal Stenosis and Nasolacrimal Duct Obstruction Following Delayed-Onset Thermal Injury - Nasution, Bryantdary Arrafif; Putra, Ardian Reza; Maulana, Muhammad (Journal La Medihealtico, 2025)
Chronic dacryocystitis represents an ordinary ophthalmologic condition that develops when the lacrimal drainage pathways become blocked thus causing ongoing epiphora and continuous painful swelling and persistent infections. Onset of blockages more frequently results from idiopathic reasons but damage to the lacrimal pathways by thermal injuries stands as an important yet unrecognized factor that leads to major clinical outcomes. Early burn treatment of the face around the eyes can trigger progressive tissue scarring of lacrimal passages that might cause long-term blockages as well as infection development. A rare case of bilateral chronic dacryocystitis exists in a 24-year-old female because she neglected facial thermal trauma she experienced during childhood. The patient experienced persistent symptoms including epiphora in both eyes together with swelling at the inner corners of her eyes and drainage consisting of mucus and pus. Both of her tear duct puncta appeared narrow while the medial corners of her eyes showed small areas of swelling. The fluorescein dye disappearance test established severe blockage in both lacrimal ducts. CT contrast imaging showed that the bilateral lacrimal sacs were enlarged while simultaneously revealing duct obstruction together with no evidence of sinonasal mass lesions. The Staphylococcus aureus with low-grade Pseudomonas aeruginosa demonstrated in microbiological culture results while elevated inflammatory markers showed systemic inflammatory activation. The patient received systemic antibiotics and corticosteroids that led to remarkable clinical improvement before surgical planning could begin. The definitive treatment chosen was external dacryocystorhinostomy (DCR) using silicone tube intubation because severe fibrosis together with septal deviation required treatment alongside polymicrobial colonization.